(untitled) (Journal of Misan Researches, 2023)
The purpose of the study is to determine whether social media platforms such as Facebook have any impact on how well students develop their vocabulary and improve motivation. The group has been assigned to the experimental group in order to monitor the development of lexical competence and motivation as they receive treatment. This group was created on Facebook by the researcher to implement the experiment to the EG by uploading educational videos and audio, drills, and other educational materials. Students in the control group, on the other hand, receive language instruction in a conventional manner. The use of a questionnaire and a pretest-posttest design is part of a mixed-methods approach. The researchers discovered statistically significant differences in vocabulary development and motivational stimulus between the experimental group and the control group after implementing the intervention. This indicates that compared to students who received the traditional method of instruction, those who received the treatment had better vocabulary development and were more motivated. It can be concluded that using Facebook in educational settings can be advantageous and useful as a tool for teaching and learning languages.